Cold Abscess in Neck Masquerading as Infected Thyroglossal Cyst: A Case Report. - Jha, Anamika; Lamichanne, Suman; Jha, Sujit (Nepalese Journal of Radiology, 2021)
Midline cystic neck swellings are often seen in younger patients and may have several causes. Sonography is the initial imaging modality followed by a Computer Tomography (CT) scan with MRI being reserved as a problem-solving tool or for preoperative extent evaluation. Pathology usually uses fine-needle aspiration cytology to confirm the diagnosis. We report a case where a cold abscess presenting as cystic midline neck swelling in a young patient, was misinterpreted as an infected thyroglossal cyst on sonography. The presence of lesions consistent with pulmonary tubercular infection helped clinch the diagnosis on the CT scan. This case also highlights the fact that whenever possible a common cause should be sought for different lesions occurring simultaneously.